Enhancing the effectiveness of Arabic language instructors in teaching communicative competence in Brunei Darussalam: a case study of the Faculty of Arabic language at Sultan Sharif Ali Islamic University (UNISSA) - Yani, Achmad; Haji Ahmad, Siti Sara; Abdullah, Rafidah; Shalihah, Siti; Thoha, Anis Malik; Nasih, Ahmad Munjin; Siraj, Taufik; Husain, Muhammad Zakir; Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi; Maghfurin, Ahmad (World Scientific and Engineering Academy Society (WSEAS), 2026)
This study examines the instructional effectiveness of Arabic language instructors in fostering communicative competence among first-year students at the Faculty of Arabic Language and Translation, Sultan Sharif Ali Islamic University (UNISSA), Brunei Darussalam. Utilizing a purposive sampling approach, data were collected from 14 students enrolled in the Communicative Arabic course during the 2024 academic year, representing 66% of the total cohort. A structured questionnaire was employed to evaluate instructional performance across seven key dimensions: oral proficiency, written proficiency, training in oral and written communication, classroom management, and motivational strategies. Descriptive statistical analysis was conducted to interpret the responses. The findings reveal a consistently high level of instructional effectiveness, with the highest student agreement (94.3%) recorded in the areas of language proficiency, oral communication training, and classroom management. These outcomes underscore the instructors’ strong pedagogical competence and mastery of linguistic content. However, slightly lower agreement levels (91.4%) were noted in the domains of motivational support for both oral and written communication, suggesting the need for enhanced learner engagement strategies. While technical proficiency and classroom organization are well-executed, the results highlight the importance of adopting more dynamic, student-centered approaches to encourage active participation and communicative confidence, particularly among passive learners. This study affirms the instructional strengths of Arabic language educators at UNISSA while identifying opportunities for targeted professional development aimed at further optimizing communicative language teaching outcomes.